Metal accumulating plants, their importance. Nickel hyperaccumulator Leucocroton havanensis Borhidi - Alfonso González, Dubiel (2020)
Over 700 of vegetable species in the world are capable of accumulating in their tissues large amounts of metal elements (Ni, Cu, Co, Cr, Mn and Zn, among others); that is why they are called metal hyperaccumulators.This physiological process has been interpreted as an adaptation of plants to the metal polluted soils where they live. Leucocroton havanensis Borhidi is an endemic Ni hyperaccumulator species of xeromorphic thorn bushes on “serpentine soils” in Cuba. Due to the high concentrations of Ni, Cr, Co, Mn, Mg and Fe, together with the low concentrations of Caand macronutrients such as N, P, and K, these metal polluted soils host a high representation of endemic plants with distinct physiological characteristics. The L. havanensis species is classified as endangered in the Red List of Cuban Flora due to the reduced amount of existing population because of human economic activity. Phytoremediation and agro-mining have been implemented in several countries within the context of sustainable development. These new technologies use hyperaccumulating plants as an alternative way to extract metals from the soil. Damage to the environment is thus avoided and the phytogenetic resources of the miningareas are preserved. The ecological function of metal hyperaccumulation may be related to the defense of these species against pathogens and herbivores. The Hyperaccumulated Ni in the leaves of Streptanthus polygaloides protect the plant from the attack of bacteria and fungi and from the Ambigolimax valentianus slugs.